Comparison of Clinico-pathologic features and outcomes of ANCA negative and ANCA positive pauci immune crescentic glomerulonephritis: A single centre study - Pallav Gupta; Vinant Bhargava; Manish Malik; Anurag Gupta; Anil K Bhalla; Ashwini Gupta; Vaibhav Tiwari; Devinder S Rana; Ramesh L Sapra (Wolters Kluwer Medknow Publications, 2024)
Introduction: Pauci-immune crescentic glomerulonephritis (PICN) is an important cause of rapidly progressive renal failure. 10-40% of PICN cases have ANCA (antineutrophil cytoplasmic antibody) negative serology. The present study compared clinico-pathologic features, Brix's renal risk score, Berden's histopathological classes and differences in outcome between ANCAnegative vs ANCA positive PICN patients. Materials and Methods: Sixty-one patients of biopsy-proven PICN were studied. Biochemical findings and ANCA serology were recorded. Renal biopsy slides were reviewed along with direct immunofluorescence. Clinical and histological features were compared between ANCA negative and positive PICN using the Man Whitney U test and Chi-square test. Patients were compared for distribution in Berden's histological classes and Brix's renal risk categories. Patient and renal survival were compared using Kaplan-Meier survival analysis. Results: ANCA negative PICN patients were younger (44.9 ± 16.5 years vs 53.6 ± 15.1 years, P = 0.049). Nasal (0 vs 18%, P = 0.035) and pulmonary involvement (9% vs 38%, P = 0.014) were lower in ANCA negative group. Both ANCA groups had similar renal biochemical profiles, percentage normal glomeruli, 16.3 ± 18.2 vs 21.7 ± 20.4 and percentage glomeruli with crescents, 64.5 ± 28.1 vs 64.3 ± 27.1. Twenty-seven per cent of ANCA negative cases fell in the sclerotic class in Berden's classification vs just 2.5% in ANCA positive group (p = 0.037) without significant difference in Brix's renal risk categories (p = 0.329). Thirteen per cent of ANCA negative patients achieved complete remission on treatment compared to 33% in ANCA positive patients. Patient survival and overall probability of progressing to ESRD were similar in the two groups. Conclusion: ANCA negative PICN cases present at younger ages. Nasal and pulmonary involvement is uncommon in these patients. Patient survival and progression to ESRD are similar in both ANCA groups.